Outcome predictors of odontogenic abscesses in the elderly - Kaercher, Daniel; Thelen, Philipp; Ruettermann, Mike; Li, Lei; Hamprecht, Axel (Frontiers in Oral Health, 2024)
Odontogenic infections have a high prevalence and can lead to severe complications. Due to demographic changes, the number of geriatric patients has increased in recent years. The aim of this study was to analyse odontogenic abscesses in elderly patients and to differentiate them from non–elderly patients regarding clinical presentation, bacterial analysis and therapy. We retrospectively reviewed 1,173 inpatients with odontogenic abscesses from 2014 to 2020. Patients were divided into elderly patients (≥70 years, n = 240) and non-elderly patients (<70 years, n = 933). Demographics, clinical parameters, laboratory values and treatment parameters were analysed. Overall, elderly patients had a longer hospital stay (LOS) (median 4 [range 28] vs. 3 [range 22] days) and more complications (9.6% vs. 7.9%) than non-elderly patients, although these differences were not statistically significant. Peri-/submandibular (p = 0.015), parapharyngeal (p < 0.001) and oral base infections (p = 0.036) were associated with significantly longer LOS in the elderly. Chronic renal failure (CRF) was associated with LOS (p = 0.010) and complications (p = 0.006). In the elderly, c-reactive protein (CRP) correlated significantly with LOS (p < 0.001) and more complications (p = 0.036). This study identifies anatomical spaces and CRF as outcome predictors of odontogenic abscesses in the elderly. In addition, CRP level may serve as a predictor of complicated course in elderly patients.